Application of a method Based in performance for the seismic analysis and design of reinforced concrete bridges (2013)
It proposes an application of a methodology that nalyzes the ability of a structural element, based on a geometric pre-dimensioning and a reinforcement supposed, finding from internal equilibrium curvatures to calculate displacements, ductility’s and seismic forces resistant, so that acceleration can be verified with the design spectrum of the seismic zone of the site, elastic or inelastic. This method allows simultaneous analysis and structural design and managing some important parameters for optimal seismic performance of bridges.